Microscopic Pattern of Bone Fractures as an Indicator of Blast Trauma: A Pilot Study. Issue 5 (10th August 2015) - Pechníková, Marketa; Mazzarelli, Debora; Poppa, Pasquale; Gibelli, Daniele; Scossa Baggi, Emilio; Cattaneo, Cristina
Abstract The assessment of fractures is a key issue in forensic anthropology; however, very few studies deal with the features of fractures due to explosion in comparison with other traumatic injuries. This study focuses on fractures resulting from blast trauma and two types of blunt force trauma (manual compression and running over), applied to corpses of pigs; 163 osteons were examined within forty fractures by the transmission light microscopy. Blast lesions showed a higher percentage of fracture lines through the Haversian canal, whereas in other types of trauma, the fractures went across the inner lamellae. Significant differences between samples hit by blast energy and those runover or manually compressed were observed (p < 0.05). The frequency of pattern A is significantly higher in exploded bones than in runover and compressed. Microscopic analysis of the fracture line may provide information about the type of trauma, especially for what concerns blast trauma.